"ChatGPT" Interaction and its Relationship with Loneliness and Social Connection in Young Adult Workers - Aprilia Mega Puspitasari; Muhammad Firas Akram; Putri Balqist Shahnaztasya; Zainun Mu’tadin (Journal of Islamic Psychology and Behavioral Sciences, 2026)
Today, AI-based technologies such as ChatGPT are becoming increasingly widespread. This development presents a new form of communication between humans and digital systems that resembles interpersonal interaction and may be associated with various psychological outcomes that can potentially affect individual psychological aspects, especially feelings of loneliness and social connectedness because it is considered to provide emotional support, information, and alternative social interactions. The main focus of this study is to examine the relationship between interaction with ChatGPT and feelings of loneliness and social connectedness among young adult workers aged 20–35 who had used ChatGPT for at least one month. The research approach used a quantitative method with a non-experimental correlational design and statistical analysis of the relationships among variables. The sample was obtained using a purposive sampling technique. Data were analyzed using Pearson Correlation and Linear Regression. The results showed that interaction with ChatGPT has no significant relationship or influence on respondents' levels of loneliness (p = 0.317). This occurs because interactions with AI tend to be utilitarian and functional, making them unable to replace emotional intimacy between humans. Conversely, interactions with ChatGPT had a very strong positive relationship (r = 0.986), explained 97.1% of the variance in social connectedness. These findings suggest that ChatGPT functions more as a cognitive aid and social facilitator that enhances individuals' confidence and readiness to interact in real-life environments, rather than as an emotional substitute for overcoming social isolation.